2022
DOI: 10.1021/acsami.2c09689
|View full text |Cite
|
Sign up to set email alerts
|

Natural Soybean Milk-Derived Bioactive Coatings for Enhanced Wound Healing

Abstract: Foodborne biomaterials, derived from diets, comprise selfassembled collections of many micro-or nanoscale units with abundant nutrients and active substances. In this study, soybean milk (SBM) was selected as a tissue engineering product for simple and feasible wound repair. SBM is a common drink prepared from soybeans and is rich in soy protein, soy isoflavones, and other bioactive components. Thus, SBM has substantial potential for antioxidation and tissue remodeling. Here, the multifunctional effect of SBM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 41 publications
0
21
0
Order By: Relevance
“…In contrast, the skin tissue of the incision treated with LA-glue was intact. Importantly, a large number of skin accessory structures, such as hair follicles and sebaceous glands, were present in the dermal tissue, and the collagen fibers were arranged in a basket-like shape similar to healthy skin tissue . Based on the restoration of the skin structure, the tensile strength, a key indicator for the quality of the newly formed tissue, recovered to a level approaching that of the normal skin (1.7 ± 0.3 MPa vs 1.8 ± 0.4 MPa), while the tensile strengths of regenerated tissue in the 3M-glue, suture, and control groups were only 1.3 ± 0.3 MPa, 1.1 ± 0.2 MPa, and 0.7 ± 0.2 MPa, respectively (Figures e and S10).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, the skin tissue of the incision treated with LA-glue was intact. Importantly, a large number of skin accessory structures, such as hair follicles and sebaceous glands, were present in the dermal tissue, and the collagen fibers were arranged in a basket-like shape similar to healthy skin tissue . Based on the restoration of the skin structure, the tensile strength, a key indicator for the quality of the newly formed tissue, recovered to a level approaching that of the normal skin (1.7 ± 0.3 MPa vs 1.8 ± 0.4 MPa), while the tensile strengths of regenerated tissue in the 3M-glue, suture, and control groups were only 1.3 ± 0.3 MPa, 1.1 ± 0.2 MPa, and 0.7 ± 0.2 MPa, respectively (Figures e and S10).…”
Section: Resultsmentioning
confidence: 99%
“…Hemolysis tests are usually used to investigate the erythrocyte compatibility of biomaterials. , The various Cu-TAn@PMS were incubated with red blood cells (RBCs) (Figure a) to investigate the RBCs’ compatibility. As shown in Figure b, the hemolysis ratios of all the microspheres are less than 1%.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, natural extracts have been widely used in biomaterials due to their excellent biocompatibility and antioxidative activities. , Among them, metal-phenolic networks (MPNs) have attracted extensive attention in constructing biomedical materials, which are constructed from natural polyphenols and a variety of metal ions, such as Fe 3+ , Cu 2+ , Zn 2+ , and Ce 3+ , thereby providing the adjustability of functionality by varying the incorporated metal ions. ,, In our previous study, we demonstrated that MPNs-based hybrid materials could integrate the merits of nanozymes and nonenzyme antioxidants to achieve multiple ROS scavenging for the treatment of sepsis, and polyphenols-based multilamellar microspheres could realize endotoxin adsorption and oxidative stress relief for septic blood purification . Therefore, inspired by their superior antioxidative activity and biological properties, we are encouraged to develop antioxidative cascade nanozymes with various metal active centers as a proof-of-concept for the alleviation of oxidative stress during extracorporeal hemoperfusion.…”
Section: Introductionmentioning
confidence: 99%
“…32 However, the heat generated from PTT still causes local tissue lesions and subsequent bacterial infections might occur in the NIR-irradiated site. 33,34 To overcome the challenge of delayed wound repair after high-temperature PTT, various strategies, such as the use of antiinflammatory, 35,36 angiogenic, [37][38][39][40] and extracellular matrix mimicking 41,42 hydrogels can be employed. However, photoactive nanomaterials that are loaded inside the hydrogels for cancer PTT can be used to locally enhance the temperature to 40 °C for the acceleration of tissue regeneration by the thermal induction of cell proliferation and angiogenesis.…”
Section: Introductionmentioning
confidence: 99%